Students and bachelors's altitudes about of the thesis like modality to choose dental surgeon's title in the san marcos's university - Madrid Chumacero, Marco Tulio (2005)
The present study's objective was to determine the attitudes oíf the students and bachelors about tue thesis as mode stop to choose Dental surgeon's title in odontology's Faculty of San Marcos's University,The aftermaths obtunds show than bachelor's bigger percentage they point out (58.4%) indifference in the attitude toward the thesis, exists 21,6%. Even when exist bordering factors stop accomplished the thesis work the bachelors hold that he is satisfactory the could have accomplished thesis work stop to choose the professional title. The student's bigger percentage they point out indifference in tue attitude toward the thesis, exists 10,59% . The factors that lirnit the thesis elaboration on the side of the students are administrative, Economic and no the academic factors, it that a fortress constitutes for the better the attitudes toward the thesis's realization as mode slop to choose the proffessional title.